THE EFFECT OF TRANSPARENCY AND INFORMATION TECHNOLOGY USE ON THE QUALITY OF FINANCIAL REPORTS OF ZAKAT MANAGEMENT ORGANIZATIONS WITH HUMAN RESOURCES COMPETENCE AS A MODERATING VARIABLE : (Study of Zakat Management Organizations in Makassar City) - Jannah, Raodahtul Odha; NUR FADHILAH S., NUR FADHILAH S.; SUMARLIN, SUMARLIN (Islamic Economic and Business Journal, 2025)
This study aims to determine the influence of transparency and the use of information technology on the quality of financial reports, as well as the role of HR competency as a moderating variable. This study was conducted at the Zakat Management Organization in Makassar City. The study used a quantitative approach with a causal comparative method. Data were collected through questionnaires from 32 respondents selected using purposive sampling techniques. Data analysis was carried out using multiple linear regression and the Moderated Regression Analysis (MRA) test using the absolute difference value approach. The results of the study indicate that transparency and utilization of information technology have a positive and significant effect on the quality of financial reports, HR competency moderates the effect of transparency on the quality of financial reports, and HR competency does not moderate the effect between the utilization of information technology on the quality of financial reports. The implications of this study underline the importance of transparency and utilization of information technology in improving the quality of financial reports so that it can increase public trust in zakat management organizations.